2008
DOI: 10.1631/jzus.b0820018
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 inhibitor inhibits hippocampal synaptic reorganization in pilocarpine-induced status epilepticus rats

Abstract: Abstract:Objective: To examine modulations caused by cyclooxygenase-2 (COX-2) inhibitors on altered microenvironments and overbalanced neurotransmitters in pilocarpine-induced epileptic status rats and to investigate possible mechanisms. Methods: Celecoxib (a COX-2 inhibitor) was administered 45 min prior to pilocarpine administration. The effects of COX-2 inhibitors on mIPSCs (miniature GABAergic inhibitory postsynaptic currents) of CA3 pyramidal cells in the hippocampus were recorded. Expressions of COX-2, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The higher dose, i.e., 10 mg/kg, has also been used in an earlier study evaluating the interaction potential of etoricoxib [20]. In different studies of COX inhibitors and seizures, the drug was administered (1) before single seizure (PTZ 60 mg/kg), which shows dosedependent effect [22]; (2) after seizures, which shows an increase in inflammation consequences; (3) prior to seizures, i.e., during the kindling, which shows protection [6][7][8]23], proconvulsant effect, or no effect [13]; and (4) prior to kindling as prophylaxis [24] resulting in increased seizure severity and mortality [10,25,26]. We used a different protocol where etoricoxib treatment was started once the kindling had been established and continued for nine days before PTZ rechallenge (subanticonvulsant dose).…”
Section: Discussionmentioning
confidence: 99%
“…The higher dose, i.e., 10 mg/kg, has also been used in an earlier study evaluating the interaction potential of etoricoxib [20]. In different studies of COX inhibitors and seizures, the drug was administered (1) before single seizure (PTZ 60 mg/kg), which shows dosedependent effect [22]; (2) after seizures, which shows an increase in inflammation consequences; (3) prior to seizures, i.e., during the kindling, which shows protection [6][7][8]23], proconvulsant effect, or no effect [13]; and (4) prior to kindling as prophylaxis [24] resulting in increased seizure severity and mortality [10,25,26]. We used a different protocol where etoricoxib treatment was started once the kindling had been established and continued for nine days before PTZ rechallenge (subanticonvulsant dose).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence supports the role of IL-1 in reducing seizure threshold and epileptogenesis in the pilocarpine SE model of epilepsy [44]. Inflammatory mediators that are released from astrocytes, such as COX-2, may directly affect epileptogenesis [74,75]. TNF-α has been identified as a prominent glutamate release modulator in cultured astrocytes; [76] complex cross-talk between microglia and astrocyte during neuroinflammatory insults can influence glutamatedependent responses [77].…”
Section: Do Uncontrolled Inflammation Bbb Damage and Seizures Form mentioning
confidence: 95%
“…However, the role of COX-2 expressed by neurons has remained elusive because COX-2 is expressed in many nonneuronal cells, and the only tools available have been pharmacologic inhibitors and global knock-outs. Inhibition of COX-2 can either exacerbate (Baik et al, 1999; Kim et al, 2008; Toscano et al, 2008) or attenuate (Baran et al, 1994; Kunz and Oliw, 2001; Jung et al, 2006; Takemiya et al, 2006; Zhang et al, 2008) the neurodegeneration observed after SE depending on the strategies used to delete or inhibit COX-2. The global COX-2 knock-out mouse is more susceptible to SE (Toscano et al, 2008), preventing conclusions on the role of postseizure COX-2 induction.…”
Section: Introductionmentioning
confidence: 99%